Ingested capsaicinoids can prevent low-fat-high-carbohydrate diet and high-fat diet-induced obesity by regulating the NADPH oxidase and Nrf2 pathways - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Ozdemir, Oguzhan; Juturu, Vijaya (Dove Medical Press Ltd, 2017)
Objective: Capsaicinoids (CAPs), most commonly found in chili peppers, have a multitude of pharmacological and physiological effects, such as anti-inflammation, antioxidant, and anticancer effects. In the present study, we set out to investigate the hypothesis that CAPs mitigate obesity in rats and the possible mechanisms thereof. Materials and methods: Rats were divided into six groups, including control (+/- 10 mg CAPs/kg body weight [BW]), low-fat-high-sucrose diet (+/- 10 mg CAPs/kg BW), and high-fat diet (+/- 10 mg CAPs/kg BW). Blood samples and liver and aortic tissues were taken at the end of the study. Results: CAPs supplementation significantly reduced hyperglycemia and hyperlipidemia (P<0.001) and ameliorated oxidative damage by reducing malondialdehyde concentrations in serum and liver and by increasing total antioxidant capacity in serum induced by the low-fat-high-sucrose and high-fat diets (P<0.001 for all). CAPs also depressed levels of NF kappa B p65, gp91(phox), and p22(phox), essential components of NADPH oxidase, in the aorta of rats. However, levels of Nrf2, Sirt1, and endothelial nitric oxide synthase were significantly increased in the aorta. Conclusion: CAPs may at least partially reduce adverse effects due to high-fat diet and sucrose consumption through regulation of energy metabolism, oxidative stress, and proteins involved in vasoprotection.
Keywords: capsaicinoids; metabolism; oxidative stress; lipid profile; antioxidant capacity